Intervención optométrica en paciente femenino de 16 años de edad con astigmatismo. - Párraga Saldivia, Kevin Alfredo (2024)
The World Health Organization estimates that 40% of the world's population has astigmatism (WHO, 2019) and more than half of the population has some type of ametropia, due to excessive use of electronic devices. Ametropias are refractive problems that do not allow light to focus correctly on the retina, causing blurring or distortion at far and near distances. Astigmatism is one of the conditions that is part of this group. The present case involves a 16-year-old female patient with astigmatism, the index patient who experienced the following symptoms: Headache, Blurred and distorted vision, Double vision, Fatigue, Visual fatigue. According to the clinical picture, the refractive status of the eyeball is examined and the binocular visual acuity of 20/60 is calculated. The optometric tests performed are: Distance and near visual acuity with and without correction, pupillary reflexes, ocular motility, objective and subjective refraction, among other tests necessary to confirm the diagnosis. Once verified, various corrective treatment options were proposed, according to the patient's need and preference, the treatment selected was the use of conventional single field of vision lenses with Photochromic blue block protection with the prescription obtained. The patient's response was favorable, achieving optimal visual acuity of 20/20. As a recommendation, the importance of attending regular visual controls is suggested.